The Influence of Transformational Leadership and Work Environment on Employee Productivity in the No Sew Department at PT Adis Dimension Footwear in Tangerang Regency - Irawan, Ricki; Sudinta, Heru; Setiawan, Temmy (UJoST- Universal Journal of Science and Technology, 2026)
This study aims to determine the simultaneous influence of transformational leadership and the work environment on the work productivity of employees in the No-Sew department at PT Adis Dimension Footwear, Balaraja, Tangerang.This study used a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all No-Sew employees at PT Adis Dimension Footwear, Balaraja, Tangerang. The sample size was 70 respondents. This study used a saturated sampling technique due to the small population size. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) transformational leadership has a significant partial t-test effect on the work productivity of employees in the No-Sew department at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (5.426>1.996) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, the work environment significantly influences the work productivity of No Sew employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.121>1.996) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, transformational leadership and the work environment significantly influence the performance of No Sew employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (58.705>3.13) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that transformational leadership and work environment variables, either partially or simultaneously, have a significant influence on the work productivity of No Sew employees at PT. Adis Dimension Footwear Balaraja-Tangerang.